Being itself: On German selbst in synthetic compounds - Livio Gaeta; Marco Angster (Zeitschrift für Wortbildung)
German synthetic compounds containing selbst have traditionally been treated as reflexive in nature. However, this view cannot cope on the one hand with the basic value of selbst as focus particle and not as pronoun and on the other with the non-reflexive value of many compounds whose meaning range from purely intensification of the understood agent of the activity as in Selbstbau ‘do-it yourself-construction’ to anti-causativity like Selbstentzündung ‘self-ignition’. In this paper, we will consider a different option, namely to interpret the focus particle selbst as a flag for signaling contrastive coreference. This option can be concretely operationalized in constructional terms as a case of constructional idiom.